A computational model of upper airway respiratory function with muscular coupling. Issue 6 (26th April 2022) - Ilegbusi, Olusegun J.; Kuruppumullage, Don Nadun S.; Schiefer, Matthew; Strohl, Kingman P.
Abstract: A two dimensional finite element model of upper airway respiratory function was developed emphasizing the effects of dilator muscular activation on the human retro-lingual airway. The model utilized an upright mid-sagittal computed tomography of the human head and neck to reconstruct relevant structures of the tongue, mandible, and the hyoid-related soft tissues, along with the retro-lingual airway. The reconstructed geometry was divided into fluid and solid domains and discretized into finite element (FE) meshes used for the computational model. Three cases were investigated: standing position; supine position; and supine position coupled with dilator muscle activation. Computations were performed for the inspiration stage of the breathing cycle, utilizing a fluid-structure interaction (FSI) method to couple structural deformation with airflow dynamics. The spatio-temporal deformation of the structures surrounding the airway wall were predicted to be in general agreement with known changes from upright to supine posture on luminal opening, as well as the distribution of airflow. The model effectively captured the effects of muscular stimulation on the upper airway anatomical changes, the flow characteristics relevant to airway reduction in the supine position and airway enlargement with muscle activation. The smallest airway opening in the retro-lingual section is predicted to occur at the epiglottic region in all the three cases considered, an unexpected vulnerable location of airway obstruction. The model also predicted that hyoid displacement would be associated with recovery from airway collapse. This information may be useful for building more complex models relevant to mechanisms and clinical interventions for obstructive sleep apnea.